Vascular Endothelial Growth Factor (VEGF)-Induced Retinal Vascular Permeability Is Mediated by Intercellular Adhesion Molecule-1 (ICAM-1) - Miyamoto, Kazuaki (American Society for Investigative Pathology, 2000)
Two prominent vascular endothelial growth factor (VEGF)-induced retinal effects are vascular permeability and capillary nonperfusion. The mechanisms by which these effects occur are not completely known. Using a rat model, we show that intravitreous injections of VEGF precipitate an extensive retinal leukocyte stasis (leukostasis) that coincides with enhanced vascular permeability and capillary nonperfusion. The leukostasis is accompanied by the up-regulation of intercellular adhesion molecule-1 expression in the retina. The inhibition of intercellular adhesion molecule-1 bioactivity with a neutralizing antibody prevents the permeability and leukostasis increases by 79% and 54%, respectively. These data are the first to demonstrate that a nonendothelial cell type contributes to VEGF-induced vascular permeability. Additionally, they identify a potential mechanism for VEGF-induced retinal capillary nonperfusion.